Enhanced Bacterial Growth and Gene Expression of D-Amino Acid Dehydrogenase With D-Glutamate as the Sole Carbon Source - Naganuma, Takeshi; Iinuma, Yoshiakira; Nishiwaki, Hitomi; Murase, Ryota; Masaki, Kazuo; Nakai, Ryosuke (Frontiers in Microbiology, 2018)
In a search for life-supporting, not life-assisting, D-amino acid metabolism, an environmental strain that grows better with D-glutamate as the sole carbon source was isolated from an ordinary river. The strain, designated as A25, exhibited a faster growth rate and greater cell yield with D-glutamate than with L-glutamate. Conversely, the D/L ratio of total cellular glutamate was as low as 4/96, which suggests that D-glutamate is more likely catabolized than anabolized. Strain A25 was phylogenetically most closely related to the gamma-proteobacterial species Raoultella ornithinolytica, with a 16S rRNA gene sequence similarity of 100%. A standard strain, R. ornithinolytica JCM 6096T, also showed similarly enhanced growth with D-glutamate, which was proven for the first time. Gene expression of the enzymes involved in D-amino acid metabolism was assayed by reverse-transcription quantitative PCR (RT-qPCR) using specifically designed primers. The targets were the genes encoding D-amino acid dehydrogenase (DAD; EC 1.4.99.1), glutamate racemase (EC 5.1.1.3), D-glutamate oxidase (EC 1.4.3.7 or EC 1.4.3.15), and UDP-N-acetyl-α-D-muramoyl-L-alanyl-D-glutamate ligase (EC 6.3.2.9). As a result, the growth of strains A25 and R. ornithinolytica JCM 6096T on D-glutamate was conspicuously associated with the enhanced expression of the DAD gene (dadA) in the exponential phase compared with the other enzyme genes. Pseudomonas aeruginosa is also known to grow on D-glutamate as the sole carbon source but to a lesser degree than with L-glutamate. A standard strain of P. aeruginosa, JCM 5962T, was tested for gene expression of the relevant enzymes by RT-qPCR and also showed enhanced dadA expression, but in the stationary phase. Reduction of ferricyanide with D-glutamate was detected in cell extracts of the tested strains, implying probable involvement of DAD in the D-glutamate catabolizing activity. DAD-mediated catalysis may have advantages in the one-step production of α-keto acids and non-production of H2O2 over other enzymes such as racemase and D-amino acid oxidase. The physiological and biochemical importance of DAD in D-amino acid metabolism is discussed.